2001
DOI: 10.1017/s095283690100108x
|View full text |Cite
|
Sign up to set email alerts
|

Jumping spiders (Araneae: Salticidae) that feed on nectar

Abstract: Nectivory was studied in 90 species from the spider family Salticidae. Observations of 31 of these species feeding on nectar from¯owers in nature was the impetus for laboratory tests in which all 90 species fed from¯owers. That sugar, not just water, is relevant to salticids was implied by choice tests where salticids spent more time drinking from a simulated nectar source (30% sucrose solution) than from distilled water. Our ®ndings suggest that nectar feeding may be widespread, if not routine, in salticid sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 26 publications
3
65
0
3
Order By: Relevance
“…Consistent with how nectar feeding appears especially common among salticids (Jackson et al 2001), we have observed that juveniles, adult males and adult females of E. culicivora in the field sometimes press their chelicerae into L. camara flowers or into the extra-floral nectaries of R. communis, with these most likely being instances of the spider feeding on nectar. We also observed this when E. culicivora was given access to L. camara and R. communis in the laboratory (Fig.…”
Section: Introductionsupporting
confidence: 78%
“…Consistent with how nectar feeding appears especially common among salticids (Jackson et al 2001), we have observed that juveniles, adult males and adult females of E. culicivora in the field sometimes press their chelicerae into L. camara flowers or into the extra-floral nectaries of R. communis, with these most likely being instances of the spider feeding on nectar. We also observed this when E. culicivora was given access to L. camara and R. communis in the laboratory (Fig.…”
Section: Introductionsupporting
confidence: 78%
“…), which also dominate the ants' diet [6][7][8]. Although no other spiders are known to rely as heavily on herbivory as B. kiplingi, many spiders do supplement a predatory diet with nectar taken from the floral or extrafloral nectaries of plants (e.g., [9][10][11][12]). …”
Section: Introductionmentioning
confidence: 99%
“…Presence of fructose was confirmed using cold-anthrone testing, a procedure developed by Van Handel [15,16] for detecting the presence of fructose in mosquitoes. While field and laboratory observations suggest that nectarivory might be especially prevalent among jumping spiders ( Figure 1) [12,17], only one species (Plexippus selipes) has been shown to be fructose positive by coldanthrone testing [14].…”
Section: Introductionmentioning
confidence: 99%
“…Salticid spiders were observed preying on species other than Guayaquila on plants with flowers, so the wider range of prey species on plants with flowers may reduce the risk of predation for the treehoppers (cf., Krebs & Davies, 1993). Second, spiders may feed on nectar (Jackson et al, 2001). Moreover, the adults of predatory syrphids and most parasitoid wasps feed on nectar and/or pollen (Jervis & Kidd, 1996).…”
Section: Discussionmentioning
confidence: 99%